A new IUCN Red List of the bryophytes of Britain, 2023. (2nd October 2022) - Callaghan, Des A.
ABSTRACT: Introduction: Britain supports one of the richest bryophyte floras in Europe. Following previous assessments in 2001 and 2011, the aim of this study was to provide a new IUCN Red List of the bryophytes of Britain. Methods: Following IUCN guidance, all species known to have occurred in Britain since ad 1500 ( n  = 1097) were assessed based on a comprehensive review and synthesis of available information. Various new measures are provided here for all species, such as the number of subpopulations, area of occupancy, and extent of occurrence, in addition to national population estimates for 181 species. Results are compared with the previous Red List assessment of 2011. Key results and conclusions: Species were categorised as Regionally Extinct (RE, n  = 4), Not Applicable (NA, n  = 23), Data Deficient (DD, n  = 45), Critically Endangered (CR, n  = 59), Endangered (EN, n  = 52), Vulnerable (VU, n  = 80), Near Threatened ( n  = 39) or Least Concern ( n  = 795). Excluding those in DD, NA or RE, 19% ( n  = 191) of bryophyte species in Britain are threatened with extinction (i.e. are in CR, EN or VU). Of the 59 species in the highest extinction risk category (CR), it is possible that 20 (34%) are already extinct. Of the 143 species included in the previous assessment in a threatened category (CR, EN or VU), 85 (69%) have been transferred to a new category, mainly because of new information on the status of the species.